Health system reform and the role of field sites based upon demographic and health surveillance - Tollman, S.M. (2000)
Explores the characteristics and defining features of field sites for demographic and health surveillance in low-income and middle-income countries. Argues that many currently active sites have a largely untapped potential for contributing substantially to national and subnational health development.